PENGARUH LATIHAN OREGON SHIFT DRILL TERHADA KELINCAHAN PADA TIM SEPAKBOLA MADRASAH TSANAWIYAH HAYATUL ISLAM KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Juita, Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT Result the indetification problem that football team Mts hayatul Islam districts Pangean Singingi Kuantan district has not had a good physical condition especially agility ( agility ) . This is because lack of exercise leads to physical conditions proficiency level . By because aims to determine whether there are effects of exercise on the Oregon Shift agility drills ( agility ) on students football team in Mts hayatul Islam districts Pangean Singingi Kuantan district . Issues raised in this study is